Resilience in the planning of rail engineering work - Ferreira, Pedro N.P. (2011)
The railway industry is today broadly recognised as a complex sociotechnical system that operates under considerable pressures for increased capacity and reliability. These pressures impact across the industry, in particular on rail engineering because of its responsibility in providing and maintaining the rail infrastructure. Within rail engineering, there is a growing need to address safety and operational risks emerging from high complexity.